2015
DOI: 10.1016/j.devcel.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

The BASL Polarity Protein Controls a MAPK Signaling Feedback Loop in Asymmetric Cell Division

Abstract: SUMMARY Cell polarization is linked to fate determination during asymmetric division of plant stem cells, but the underlying molecular mechanisms remain unknown. In Arabidopsis, BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL) is polarized to control stomatal asymmetric division. A MITOGEN-ACTIVATED PROTEIN KINASE (MAPK) cascade determines terminal stomatal fate by promoting the degradation of the lineage determinant SPEECHLESS (SPCH). Here we demonstrate that a positive feedback loop between BASL and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
199
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(205 citation statements)
references
References 73 publications
1
199
0
1
Order By: Relevance
“…By contrast, bubblin abolishes the asymmetry of cell division and causes stomatal precursor clustering, suggesting that bubblin acts on cell polarity independently of extrinsic signaling. Meristemoid cell polarity is generated by BASL that localizes to the cell periphery and is predicted to regulate SPCH degradation (Zhang et al, 2015). Bubblin induced stomatal lineage cells to divide without establishing BASL polarity, and this accounted for the retention of SPCH, which resulted in stomatal clustering (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, bubblin abolishes the asymmetry of cell division and causes stomatal precursor clustering, suggesting that bubblin acts on cell polarity independently of extrinsic signaling. Meristemoid cell polarity is generated by BASL that localizes to the cell periphery and is predicted to regulate SPCH degradation (Zhang et al, 2015). Bubblin induced stomatal lineage cells to divide without establishing BASL polarity, and this accounted for the retention of SPCH, which resulted in stomatal clustering (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral localization of BASL requires MPK3/ 6-mediated phosphorylation (Zhang et al, 2015). Bubblin might act as a kinase inhibitor to perturb BASL phosphorylation or regulate the targeting of phosphorylated BASL to the cell periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This slow mobility of BASL was specific to the polar site since BASL localised to non-polar sites on the PM showed greater mobility, demonstrating that distinct mechanisms may direct or retain BASL at polar versus non-polar sites. Targeting to the polar site requires phosphorylation of BASL by MPK3/6 [15]. By mutating the MAPK phosphorylation sites in BASL with phospho-mimicking residues, FRAP analysis demonstrated that BASL phosphorylation actually reduces mobility at the polar PM site, which has significant consequences.…”
Section: Mutations In Breaking Of Asymmetry In the Stomatal Lineagementioning
confidence: 99%
“…BASL is phosphorylated by MPK3/6, and this facilitates BASL functioning as a scaffold for YDA at the plasma membrane (PM) [15]. Prior to the ACD of a MMC, BASL localises to both the nucleus and the cell periphery distal to the future division plane of the MMC, and is therefore predictive of the future ACD plane.…”
Section: Mutations In Breaking Of Asymmetry In the Stomatal Lineagementioning
confidence: 99%